1987
DOI: 10.1046/j.1537-2995.1987.27187121482.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl iron for short‐term supplementation in female blood donors

Abstract: A randomized, double-blind trial of iron replacement after repeated blood donation was conducted in 75 menstruating women; 51 completed the study. Volunteers were assigned randomly to one of three treatment groups: 1) carbonyl iron (nontoxic elemental iron powder), 600 mg; 2) ferrous sulfate, 300 mg (60 mg Fe++); or 3) placebo, each given three times daily for 1 week immediately after blood donation. Blood samples obtained initially and 56 days later were tested for hemoglobin, mean corpuscular volume (MCV), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 18 publications
5
34
1
Order By: Relevance
“…Out of total 57 (28.5 %) of donors had Hb \12.5 gm/dl detected by hematology analyzer on venipuncture sample. Similar results were also observed in other studies [9][10][11]. Variation observed in the study by Magsudhlu et al [11] was 7.7 %.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Out of total 57 (28.5 %) of donors had Hb \12.5 gm/dl detected by hematology analyzer on venipuncture sample. Similar results were also observed in other studies [9][10][11]. Variation observed in the study by Magsudhlu et al [11] was 7.7 %.…”
Section: Discussionsupporting
confidence: 91%
“…The similar results were also observed by Mittal et al [4] as significant mean decrease (p \ 0.001) in serum ferritin after three blood donations per year, the values being 21.36 versus 55.5 ng/ ml in those donors who came for the first time. Similar results were also observed by other investigators [9,12] The reason for iron deficiency in donors with repeated donations is that the iron demand increases with number of annual blood donation which cannot be compensated by iron absorption and results in an iron deficiency [13]. The prevalence of iron deficiency is related to frequency of blood donation rather than to cumulative total of donations [4,13].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…7 Gastrointestinal troubles, with a frequency of up to 30% as described by Al-Momen et al have been reported in patients groups treated with oral iron (carbonyl iron).Carbonyl iron showed a better rise in haemoglobin more than ferrous sulphate in a study conducted by Gordeuk et al 8 According to Kochchar PK et al, response to therapy with parenteral iron is similar to that with oral iron. 9 The haemoglobin rises at a similar rate, although stores will be replenished more efficiently with parenteral iron (iron sucrose).…”
Section: 436mentioning
confidence: 92%
“…The human absorption of iron from such powders has been difficult to assess because powders isotopically prepared for research do not match the physical characteristics of their commercial counterparts (7)(8)(9)(10)(11)(12)(13)(14)(15). Human efficacy studies, testing for improvements in iron status with the elemental iron powders, have been limited, and showed benefits of carbonyl iron in supplemental doses (16)(17)(18)(19) and of electrolytic iron (;14-17 mg/d) provided to infants in cereal (20) but yielded mixed results with reduced iron added to bread flour (21).…”
Section: Introductionmentioning
confidence: 99%